Building wireless sensor networks application using Sun SPOTs - Shaikh, Asadullah; Anjum, Naveed; Samad, Fahad; Shah, Asadullah (2012)
Wireless Sensor and Mobile ad-hoc Networks are character- ized by their highly dynamic, multi-hop, and infrastructure-less nature. In this dynamic environment, different nodes, oering dierent services, may enter and leave the network at any time. Ecient and timely ser- vice discovery is a requirement for good utilization of shared resources in this kind of network. Service discovery is not a new problem. Many academic and industrial researchers have proposed numerous solutions (protocol/middleware) of service discovery for both wired and wireless networks. The wireless sensor networks have several characteristics that set them apart from the traditional wired networks. Hence, classical ser- vice discovery protocols in sensor networks are not applicable. This paper presents a service oriented architecture for autonomous wireless sensor networks that provide various services at dierent levels